THE PHENOMENON OF THE UKRAINIAN DIASPORA: THE PROBLEM OF PRESERVING ETHNIC IDENTITY AND DEVELOPMENT - Ірина Валеріївна Підкуркова; Анна Володимирівна Гой (Вісник НЮУ імені Ярослава Мудрого: Серія: Філософія, філософія права, політологія, соціологія, 2020)
Problem setting. Ethnic communities such as the diaspora are formed on the basis of national consolidation processes farfrom the historical homeland. The main question they need